2021
DOI: 10.3390/jcm10143183
|View full text |Cite
|
Sign up to set email alerts
|

Review of Rhinitis: Classification, Types, Pathophysiology

Abstract: Rhinitis describes a pattern of symptoms as a result of nasal inflammation and/or dysfunction of the nasal mucosa. It is an umbrella entity that includes many different subtypes, several of which escape of complete characterization. Rhinitis is considered as a pathologic condition with considerable morbidity and financial burden on health care systems worldwide. Its economic impact is further emphasized by the fact that it represents a risk factor for other conditions such as sinusitis, asthma, learning disabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
63
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 61 publications
1
63
0
2
Order By: Relevance
“…The pathophysiology of AR involves the activation of an inflammation cascade that is initiated by mast cell activation succeeding IgE cross-linking by an allergen. This action triggers the degranulation of mast cells and the release of preformed mediators such as histamine [ 5 , 6 ]. Histamine is a vital mediator that is released during the immediate allergic response from cytoplasmic granules in tissue mast cells and during the late phase response chiefly from recruited basophils.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathophysiology of AR involves the activation of an inflammation cascade that is initiated by mast cell activation succeeding IgE cross-linking by an allergen. This action triggers the degranulation of mast cells and the release of preformed mediators such as histamine [ 5 , 6 ]. Histamine is a vital mediator that is released during the immediate allergic response from cytoplasmic granules in tissue mast cells and during the late phase response chiefly from recruited basophils.…”
Section: Introductionmentioning
confidence: 99%
“…Histamine is a vital mediator that is released during the immediate allergic response from cytoplasmic granules in tissue mast cells and during the late phase response chiefly from recruited basophils. The rapidly synthesized mediators trigger the early symptoms of AR: sneezing, pruritus, and rhinorrhea [ 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is classified into many subtypes according to the causative agent such as viral or bacterial infections and allergies [ 1 ]. However, many cases illustrate the interchanging properties of these subtypes as displayed by conversion of a type into another in addition to the presence of multiple subtypes in a single case [ 2 , 3 ]. The key factor in tackling rhinitis is identifying the type(s) and severity which in turn will vary the treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Allergic diseases are immunoglobulin E (IgE)-mediated type I inflammatory disorders, including allergic rhinitis [1,2]. The major symptoms of allergic rhinitis are sneezing, nasal congestion, and lacrimation caused by complex allergen-driven mucosal inflammations, and the increased inflammatory mediators lead to sensory nerve activation, plasma leakage, and congestion [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The major symptoms of allergic rhinitis are sneezing, nasal congestion, and lacrimation caused by complex allergen-driven mucosal inflammations, and the increased inflammatory mediators lead to sensory nerve activation, plasma leakage, and congestion [3,4]. The prevalence of these diseases in the USA ranges from 9 to 42%, and in the UK, it reaches 26% in adults [1,5]. An epidemiological study in Japan revealed that the prevalence of allergic rhinitis markedly increased from 29.8 to 39.4%, between 1998 and 2008 [6].…”
Section: Introductionmentioning
confidence: 99%